Długi Rok Miłosza w Bułgarii i Rodzinna Europa. Przekład tytułu Rodzinnej Europy jako motyw analizy literackiej - Grigorowa, Margreta (Postscriptum Polonistyczne, 2020)
The article presents an account of reception facts that demonstrate how the celebration of the anniversary of Miłosz's in Bulgaria in 2011 was not limited to one year only, but continued into the next. Such a long ‘anniversary celebration’ signals how well received Miłosz was in Bulgaria. The Bulgarian edition of Native Realm (Rodzinna Europa) and its publication can be found within the context of this prolonged commemoration. The translation of the title itself which focuses on the two metaphors describing Europe can lead to a critical investigation; native space and family. The article argues that Miłosz's autobiographical book shows the implications of Europe as a native space in terms of culture and nature.